Urgensi Pendidikan Keluarga Islam Dalam Mengatasi Perilaku Remaja Pada Era Metaverse - Tuti Nuriyati; Desi Arpa; Siti Munawarah (Akademika: Jurnal Keagamaan dan Pendidikan, 2023)
This study discusses the urgency of Islamic family education to improve adolescent behavior in the metaverse era, because many young people today do not follow the correct norms due to the lack of education from their families. The purpose of this study is to determine the behavior of adolescents in the metaverse era and the importance of family education to improve their behavior. This research methodology uses qualitative research with data collection techniques through observation, interviews and documentation as well as data analysis with descriptive analysis. The results of this study are that Islamic family education is very important to educate and improve the behavior of adolescents in the metaverse era because family education has a very large impact on adolescents.